Sosialisasi Pencegahan Virus Covid 19 Di Masyarakat - Yunicho Yunicho; Noviponi Harwani (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
The global impact of the covid-19 pandemic demanded the government and society to survive in the face of the Covid-19 pandemic so that people eventually have to return to their usual activities. The spread of cases caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus is very fast so it needs to be handled as soon as possible such as prevention efforts. In facing the new normal condition, people's behavior and actions must change completely from the usual ones that are often done. This activity is in order to help people in Sukamaju District face New Normal conditions so that people can carry out activities while adhering to health protocols. Methods of implementing community service are carried out by providing direct socialization regarding efforts to prevent the spread of covid-19. The result of this service activity is that the people of Sukamaju District have the knowledge and ability to prevent the spread of Covid-19 and are more alert and calm in facing new conditions.